Two pairs of twins pursued their studies in UMP - UMP, PNC (2019)
Two pairs of twins quickly became the centre of attraction during the registration of new students for the bachelor’s degree programme for the academic year of 2019/2020 held at Universiti Malaysia Pahang (UMP) on September 2, 2019.